Clinical efficacy of probiotics in the treatment of diabetes kidney disease: a systematic review and meta-analysis - Liu, Liangjing; Liu, Haolan; Mao, Xiaoling; Li, Chao; Yan, Weitong; Ou, Zhongmin; Li, Xianhui (Frontiers in Microbiology, 2026)
ObjectiveDiabetic kidney disease (DKD) is a major microvascular complication of diabetes and the leading cause of end-stage renal disease. Growing evidence suggests that gut microbiota dysbiosis may contribute to DKD progression, and probiotics have been proposed as a potential adjunctive therapy. However, existing clinical findings remain inconsistent, with some trials reporting benefits in blood urea nitrogen (BUN), estimated glomerular filtration rate (eGFR), and glycosylated hemoglobin (HbA1c), while others show no significant improvements. This study aimed to systematically evaluate the clinical efficacy of probiotics in patients with DKD.MethodsRelevant randomized controlled trials (RCTs) were identified through PubMed, Embase, Web of Science, the Cochrane Library, and the Chinese Science Citation Database up to October 2025. Data were synthesized using RevMan 5.3 and Stata 16.0. The risk of bias was assessed using the Cochrane Risk of Bias tool version 1.0 (RoB 1.0), publication bias was evaluated with Egger’s test, and the certainty of evidence was graded according to the GRADE approach.ResultsSeven RCTs involving 502 participants were included. Meta-analysis showed that probiotics significantly reduced serum creatinine [mean difference (MD) −0.09 mg/dL, 95% confidence interval (CI) −0.14 to −0.04], BUN (MD −1.58 mg/dL, 95% CI −2.80 to −0.36), fasting blood glucose (MD −0.48 mmol/L, 95% CI −0.89 to −0.07), triglycerides (MD −19.17 mg/dL, 95% CI −35.14 to −3.20), total cholesterol (MD −11.68 mg/dL, 95% CI −20.37 to −2.99), low-density lipoprotein cholesterol (MD −12.72 mg/dL, 95% CI −18.76 to −6.67), high-sensitivity C-reactive protein (MD −1.59 mg/L, 95% CI −2.31 to −0.88), and malondialdehyde (MD −0.52 μmol/L, 95% CI −0.91 to −0.13). No significant effects were observed on 24-h urine protein, eGFR, 2-h postprandial blood glucose, HbA1c, insulin, high-density lipoprotein cholesterol, or total antioxidant capacity. Egger’s test indicated no significant publication bias for most outcomes, except for potential bias in eGFR. The certainty of evidence ranged from moderate to very low, and the strength of recommendation was strong.ConclusionProbiotic supplementation may improve renal function, glycemic control, lipid metabolism, and inflammation/oxidative stress in DKD patients. Further large, high-quality RCTs are warranted to confirm these findings.